The habit of buying foods announced on television increases ultra-processed products intake among schoolchildren - Raphaela Silveira Fraga; Sarah Liduário Rocha Silva; Luana Caroline dos Santos; Luana Rosa de Oliveira Titonele; Ariene da Silva Carmo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2020)
Abstract: This study aimed to verify the effects of buying television advertised food in schoolchildren eating behaviors. We performed a cross-sectional study with fourth grade students of an elementary education in Belo Horizonte, Minas Gerais State, Brazil. We analyzed anthropometric data, the habit of buying television advertised food/beverages, and food consumption (two 24-hour dietary recalls). Logistic regression models were conducted and adjusted for gender, age, caloric intake, nutritional status, and social deprivation of area of residence. In total, 797 children were evaluated, the mean age was 9.81 (0.59) years, 50.7% were female, and 32.4% overweight. The prevalence of the habit of buying television advertised food was 43.1%, among which 99.3% concerned ultra-processed foods, according to the classification proposed by Monteiro et al. (2016), mainly milk beverages (12.1%), industrialized biscuits (11.5%) and candies (9.5%). The habit of buying advertised food increased the chance of consuming ultra-processed foods (OR = 1.92; 95%CI: 1.06-3.46). We found no correlation between this habit and the consumption of minimally processed and processed foods (p < 0.05). This study findings may corroborate the debate on food advertising policy and the development of effective nutrition interventions among schoolchildren, which should involve integrated education bringing together children and parents.